Dexmedetomidine and the glymphatic system: a new perspective in managing postoperative cognitive dysfunction - Zhang, Sha-Sha; Meng, Fan-Geng; Rong, Yuan-Yuan; Zhang, Yi-Wen; Liu, Hua-Qin (Frontiers in Pharmacology, 2025)
Postoperative cognitive dysfunction (POCD) is a common and significant neurological complication, occurring more frequently in elderly individuals and those with frailty or underlying neurodegenerative conditions, though it is not limited to these populations. The glymphatic system—a brain-wide clearance network dependent on aquaporin-4 (AQP4) polarity, arterial pulsation, and sleep-driven cerebrospinal fluid (CSF)–interstitial fluid exchange—has recently emerged as a promising target for cognitive protection. Dexmedetomidine (Dex), a selective α2-adrenergic receptor agonist, facilitates glymphatic function by mimicking non-REM sleep patterns and reducing central norepinephrine tone. Preclinical studies suggest Dex enhances glymphatic clearance by promoting CSF flow, restoring AQP4 localization, and attenuating neuroinflammation, potentially reducing POCD risk. Additionally, Dex provides neuroprotection by inhibiting neuronal apoptosis and preserving blood-brain barrier integrity. Despite promising evidence, most current data are derived from animal studies, and direct clinical validation remains limited. Key challenges include inadequate clinical tools for assessing glymphatic function and the absence of standardized protocols regarding Dex dosage, timing, and patient selection. This review provides a comprehensive summary of how Dex modulates glymphatic system function, with a particular focus on its potential to prevent POCD through mechanisms such as promoting CSF flow, restoring AQP4 polarity, and attenuating neuroinflammation. It also highlights current research gaps, including the lack of direct clinical evidence, the limited availability of reliable methods to assess glymphatic function, and the absence of standardized Dex administration protocols. The review emphasizes the need for future studies to incorporate multimodal imaging, integrated mechanistic analysis, and identification of high-risk patient subgroups, in order to facilitate the clinical translation of Dex as a glymphatic-targeted neuroprotective agent.